Double Dutch Delight : uniting big men, bears & admirers in friendship. ('s Hertogenbosch : Big Dutch Girth&Mirth, 1995)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijksRedactie : PB 1112, 5200 BD ‘s Hertogenbosch
Nederlands
Periodiek